An unusual suicide by carbon monoxide intoxication: 91% HbCO saturation in a sealed setting. (2021) - Ferorelli, Davide; Mandarelli, Gabriele; Spagnolo, Lorenzo; Misceo, Federica; Strisciullo, Giuseppe; Polo, Lorenzo; Solarino, Biagio; Dell'Erba, Alessandro
Highlights: A multidisciplinary approach is mandatory to assess the cause and the manner of death in cases of suspect fatal CO inhalation. The lack of signs on the body (e.g. contusions or excoriations by convulsions) or on the scene (e.g. traces of vomiting) suggest that the lethal HbCO saturation levels have been reached in a very short time. In the present case, the particular setting of the crime scene together with the very high levels of detected HbCO saturation suggests a possible correlation between time of exposure, source of CO, and saturation levels. Abstract: Carbon monoxide (CO) is the most common lethal poison in every community yet studied. Accidental or suicidal CO poisoning has been reported as the most frequent manner of death. In the case we report here, a man was found dead inside his house with a strong smell of burning. The house presented no signs of effraction, and a lot of scotch tape was placed around the windows and doors edges as well as the keyholes to avoid any passage of air. Near the bed, there was an extinguished brazier with combusted carbon. After the external examination of the body a toxicological analysis was performed. The results pointed out 91% HbCO saturation in absence of signs of intermediate intoxication on the body or on the scene. This article aims to outline the importance of performing a multidisciplinary approach that includes an accurate crime scene investigation and a proper toxicological assessment, to evaluate the cause of death in cases of suspected CO inhalation suicide. The crime scene investigation together with the very high levels of HbCO saturation detected, suggest a possible correlation between time of exposure, source of CO, and saturation levels.